An unusually severe phenotype for familial adenomatous polyposis. Issue 5 (1st November 1997) - Eccles, D M; Lunt, P W; Wallis, Y; Griffiths, M; Sandhu, B; McKay, S; Morton, D; Shea-Simonds, J; MacDonald, F
Abstract : Familial adenomatous polyposis (FAP) is a dominantly inherited predisposition to the development of many hundreds to thousands of adenomatous polyps of the colon. The mean age of onset is around 15 years, symptoms may arise in the third decade, and the median age for the development of colonic cancer is 35–40 years. Prophylactic colectomy reduces the risk of death from colorectal cancer to such an extent that late sequelae such as upper gastrointestinal tumours have become the main cause of mortality in appropriately managed patients. The age at which colonic surveillance begins reflects the natural history of the disease. Onset of polyp formation and cancer in childhood is very unusual, but has recently been associated with a specific mutation at codon 1309 in exon 15 where a more severe phenotype is sometimes observed. The case histories of two families are reported in which there is childhood onset of polyps in the youngest generation and in one case a carcinoma, in whom mutations have been identified in exon 11 of the APC gene. Several other affected relatives were diagnosed at ages ranging from 5–48 years, some already with a cancer at the time of first screening. Since the aim of screening for colonic polyps is prevention of colonic cancer, family members at risk should be offered genetic assessment and direct mutation testing where this is possible, usually in the early teens. In the absence of a genetic test (the situation in about one third of families) or in a known gene carrier, annual colonoscopy examination is advised from the same age. Clinicians should take note of the family history and be prepared to consider much earlier intervention if symptoms occur in a child with a family history of FAP. Where childhood onset of polyps has occurred, other children at risk in the family must be offered earlier genetic testing and endoscopic surveillance.